IMPLEMENTASI PEMBELAJARAN E-LEARNING PADA MATA PELAJARAN PAI DALAM PEMBENTUKAN KARAKTER SISWA DI SDN KADEMANGAN 02 - Ika Ika; Imam Sholi Huddin; Sardi Sardi; Siti Ainun (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2022)
The use of media-based, e-learniang has now become a habit for the entire community in various aspects and also in education. One of the subjects that also requires innovation in the learning process is the subject of Islamic Religious Education.The purpose of Islamic education in schools in general is to impart knowledge about the faith, appreciation and practice of students towards religious learning, in order to make individuals fear Allah and have noble character in their lives for society and the country (Arif K,2016). In order for the objectives to be achieved, the process requires effective learning in the ose of appropriate learning strategis. Research in the method used in standardized, systematic and logical scientific research.This study uses a qualitative approach to describe the problem and focus of research online learning or better known as E-learning, namely the use of information and communication networks to support the teaching and learning process. A village consisting of several components that interact with one another, with the attachment between all of them and each other,which can realize previously defined learning objectives.Previously character education is an absolute thing that must be done because basically for all teachers, namely as educators, they have a goal the same in shaping character. Character education forms and develope the potential of students to have a good mindset, be careful good behavior, improvement and affirmation of character education, namely: inprove and strengthen the role of the family, community education unit filter function, namely character education that sorts out the nation’s own culture and spreading the culture of other nations that are not in accordance with a cultural value authoritiative nation and character of the nation.